Diligence analysis for micro grid systems in islanded mode of operation with optimal switching control of converter - Gupta, Pritha; Singh, Mahesh; Ralhan, Shimpy; Singh, Mangal (Institute of Advanced Engineering and Science, 2025)
To operate a microgrid system in islanded mode, it is essential to analyze the economic feasibility and performance of the system. The proposed system integrates two or more renewable energy sources, providing a promising solution for meeting energy needs sustainably. Conducting a techno-economic analysis of such microgrid systems is critical to maximizing the efficient utilization of renewable energy sources. The simulations for these microgrid systems are performed using HOMER Pro software, where various economic parameters—such as cost of energy (COE), electricity production, net present cost (NPC), carbon emissions, fuel consumption, and payback period—are evaluated for the proposed systems. Additionally, the system's performance is analyzed using PSIM software, which incorporates optimal switching control. The results are further validated using a prototype hardware setup. The findings indicate that the PV/hydro system with NPC: 705,658 Rs and payback period: 9.65 years is the most suitable option for meeting the electricity demand in rural areas. Also, through optimal switching control applied to the micro grid converter the output voltage achieved is seven levels and harmonic distortion is 3.7% for voltage and 1.7% for the current.